2014
DOI: 10.3233/jad-140393
|View full text |Cite
|
Sign up to set email alerts
|

Cofilin Rods and Aggregates Concur with Tau Pathology and the Development of Alzheimer's Disease

Abstract: Cofilin rods and aggregates signify events initiated early in the pathological cascade. Further definition of the mechanisms leading to their formation in the human brain will provide insights into the cellular causes of AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 35 publications
4
46
2
Order By: Relevance
“…Tau neuropil threads and cofilin pathology are both present in AD brain, but their immunostaining at high magnification does not overlap [Rahman et al, 2014]. Because rods disrupt axonal microtubules Cichon et al, 2012], we suggest the release of tau following this disruption might be the source of tau initiating the hyperphosphorylation cascade (Fig.…”
Section: Nfts and Tauopathiesmentioning
confidence: 84%
See 1 more Smart Citation
“…Tau neuropil threads and cofilin pathology are both present in AD brain, but their immunostaining at high magnification does not overlap [Rahman et al, 2014]. Because rods disrupt axonal microtubules Cichon et al, 2012], we suggest the release of tau following this disruption might be the source of tau initiating the hyperphosphorylation cascade (Fig.…”
Section: Nfts and Tauopathiesmentioning
confidence: 84%
“…In human AD brain, cofilin‐actin rods were first observed by immunohistochemistry in paraffin sections but were not found in similar sections from brains of cognitively normal subjects [Minamide et al, ]. A more recent study quantifying cofilin immunofluorescence showed rod‐like and aggregate cofilin pathology four‐fold greater in number and larger in area in human AD brain sections than in age‐matched controls [Rahman et al, ]. However, the question remains: are rods just a reporter of neurodegenerative stress or, as found in culture, a mediator of synapse loss?…”
Section: Bodymentioning
confidence: 99%
“…Although punctate, the cells retained their branching processes (Figure b). To test whether other proteins also located to Iba1 puncta, cells were double labeled with actin‐associated protein cofilin (which is known to label microglia in AD brain) . This showed that some puncta contained both Iba1 and cofilin (Figure c, arrow).…”
Section: Resultsmentioning
confidence: 99%
“…Immunolabeling was performed as previously described with minor modifications . Sections were incubated in sodium citrate buffer pH6.0 at 100°C for 10 minutes for antigen retrieval, before permeablising, blocking and then incubating in primary antibodies (Cofilin 1:500 (Sigma, cat # C8736) or total tau 1:500 (Dako) and Iba‐1 1:50 (Millipore, cat # MABN92) for 3 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The actin cytoskeleton is highly impaired in AD, with actin accumulating in aggregates . The presence of these actin‐rich inclusions correlates with the extent of tau pathology in AD patients , and tau can be detected in a subset of these rods . Given the association of hBin1 with N‐WASP and the involvement of BAR‐domain proteins in regulating actin dynamics, we speculated that hBin1 could be involved in tau pathology by directly affecting actin dynamics.…”
Section: Introductionmentioning
confidence: 99%